Twenty‐four–channel high‐impedance glove array for hand and wrist MRI at 3T. Issue 5 (31st December 2021) - Zhang, Bei; Wang, Bili; Ho, Justin; Hodono, Shota; Burke, Christopher; Lattanzi, Riccardo; Vester, Markus; Rehner, Robert; Sodickson, Daniel; Brown, Ryan; Cloos, Martijn
Abstract : Purpose: To present a novel 3T 24‐channel glove array that enables hand and wrist imaging in varying postures. Methods: The glove array consists of an inner glove holding the electronics and an outer glove protecting the components. The inner glove consists of four main structures: palm, fingers, wrist, and a flap that rolls over on top. Each structure was constructed out of three layers: a layer of electrostatic discharge flame‐resistant fabric, a layer of scuba neoprene, and a layer of mesh fabric. Lightweight and flexible high impedance coil (HIC) elements were inserted into dedicated tubes sewn into the fabric. Coil elements were deliberately shortened to minimize the matching interface. Siemens Tim 4G technology was used to connect all 24 HIC elements to the scanner with only one plug. Results: The 24‐channel glove array allows large motion of both wrist and hand while maintaining the SNR needed for high‐resolution imaging. Conclusion: In this work, a purpose‐built 3T glove array that embeds 24 HIC elements is demonstrated for both hand and wrist imaging. The 24‐channel glove array allows a great range of motion of both the wrist and hand while maintaining a high SNR and providing good theoretical acceleration performance, thus enabling hand and wrist imaging at different postures to extract kinematic information.